Complete heart block in a boy with hyperostosis–hyperphosphataemia syndrome: a case report. Issue 1 (5th February 2019) - Hosseini, Zahra; Zanjani, Keyhan Sayadpour; Eslami, Masoud; Mollazadeh, Reza
Abstract: Background: Hyperostosis–hyperphosphataemia syndrome (HHS) is a rare metabolic disorder characterized by recurrent painful swelling of long bones and periosteal new bone formation. Case summary: A 6-year-old boy was referred to our centre due to bradycardia. He was diagnosed with HHS 3 years' prior, after investigation for the cause of joint pain and genu valgum. During medical follow-up in 2013–16, the paediatric cardiologist discovered thickened and calcified mitral and aortic valves and progression of cardiac conduction disturbance from 1st degree to 3rd degree atrioventricular block (AVB). The patient died in 2017 due to multiorgan failure caused by hyperphosphataemia and ectopic calcification. Discussion: Our case is unique in that ectopic calcification occurred in the aortic, mitral valve and cardiac conduction system, and AVB progressed from 1st degree to 3rd degree over time despite treatment with high-dose phosphate binders.